Airborne concentrations of formaldehyde in a pathology unit - Ntsuba, Hlosi Samuel (My University, 2012)
Background This descriptive cross-sectional study aimed to assess the exposure to formaldehyde associated with the tasks in a pathology laboratory unit. The study objectives were to describe the tasks involving the use of formaldehyde in the unit and assess exposure to formaldehyde as well as assess the effectiveness of existing engineering/ventilation system control methods. Methods The study involved observation and description of all tasks carried out in the laboratory, assessing exposure to formaldehyde and physical measurements of laboratory parameters such as area and volume. Exposure assessment involved three levels: task-based exposure assessment; personal exposure assessment and area exposure assessment. Formaldehyde measurements, by means of shadow sampling (personal breathing zone sampling by another person shadowing person being sampled) were taken using the formaldehyde meter. Data were summarised using means, medians and proportions and results were presented in figures and tables. For significance testing, an analysis of variance was carried out on the log-transformed data and p-value less than 0.05 were interpreted as statistically significant. Results Not all tasks in the laboratory were done according to the standard operating procedures. In general, exposure to formaldehyde was highest among the assistants group who were mostly responsible for high-exposure tasks. Mean STEL values for assistants, technologists and pathologist were 2.37ppm, 1.21ppm and 1.59ppm respectively, while for TWA, the figures were 0.60ppm, 0.36ppm and 0.21ppm. For short term exposures (STEL and peak values) pathologist exposure levels were higher than those of technologists while technologists were higher for long term exposures (daily exposure and 8-hour TWA). Daily exposure varied significantly for assistants and technologists but not for pathologist. Despite the use of engineering exposure controls for formaldehyde, 27/28 of all tasks were higher than the ACGIH threshold ceiling limit of 0.3ppm, 0.008ppm MRL value and 0.002ppm RELTWAConclusion The results have shown exposures among the employees of all job categories in this study, with laboratory assistants being the most exposed. Currently installed local ventilation system requires to be upgraded in accordance with best practices of 3.5m/s for air speed. Training, on PPE usage together with the medical surveillance should also be implemented. value.
Keywords: Environmental Monitoring--methods; Air Pollutants; Air Pollutants, Occupational